2022
DOI: 10.1126/scitranslmed.abn3041
|View full text |Cite
|
Sign up to set email alerts
|

The anti–SARS-CoV-2 monoclonal antibody bamlanivimab minimally affects the endogenous immune response to COVID-19 vaccination

Abstract: As the coronavirus disease 2019 (COVID-19) pandemic evolves and vaccine rollout progresses, the availability and demand for monoclonal antibodies for the prevention and treatment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are also accelerating. This longitudinal serological study evaluated the magnitude and potency of the endogenous antibody response to COVID-19 vaccination in participants who first received a COVID-19 monoclonal antibody in a prevention study. Over the course of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…There were no differences in non-RBD IgG titers between the mAb and placebo groups at day 28. In contrast, it was found that following a higher (4200 mg), prophylactic dose of bamlanivimab, individuals without a history of SARS-CoV-2 infection had lower antibody titers after two doses of a COVID-19 mRNA vaccine than individuals who had received placebo control (5). However, antibody titers differed between the groups by twofold or less, which was considered a clinically insignificant difference (5).…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in non-RBD IgG titers between the mAb and placebo groups at day 28. In contrast, it was found that following a higher (4200 mg), prophylactic dose of bamlanivimab, individuals without a history of SARS-CoV-2 infection had lower antibody titers after two doses of a COVID-19 mRNA vaccine than individuals who had received placebo control (5). However, antibody titers differed between the groups by twofold or less, which was considered a clinically insignificant difference (5).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed, as did one prior study, a decrease in IgG Abs to some SARS-CoV-2 Ags in children but not adults (4), but the prior study did not evaluate nAbs, which we show decreased less frequently in children than adults. We used a surrogate neutralizing assay in this study that was previously been reported to be strongly correlated with levels of nAb measured with pseudovirus assays (20). Two prior studies showed lower nAb titers in children than adults with SARS-CoV-2 infection, one of which included only hospitalized children (11) and the other included hospitalized children and children with asymptomatic infection (17).…”
Section: Discussionmentioning
confidence: 99%
“…Luminex xMAP technology is a multiplex, flow cytometrybased platform that allows the simultaneous quantitation of many protein analytes in a single reaction (18). A custom Luminex-based assay was developed to measure serology and Ab ACE2receptor-binding domain (RBD) binding inhibition in a single assay as previously described (19,20). Surrogate nAbs.…”
Section: Serological Assaysmentioning
confidence: 99%
“…These results emphasize the utility of mAbs regardless of the proportion vaccinated, and have public health implications regardless of the pandemic source; as the effective reproductive number, R ( t ), approaches 1, incremental benefits from an antiviral may still provide momentum in further reducing infections, thereby bringing R ( t ) below 1. Recent evidence also suggests that receiving a mAb for COVID‐19 prophylaxis does not affect the immune response that results from subsequent vaccination, 34 strengthening the combined role for these strategies in pandemic management.…”
Section: Discussionmentioning
confidence: 99%